Dissemination of Organic Waste Crushing Machine Technology to Accelerate the Competitiveness of Zero Waste-Based Farming Businesses - Nurrohkayati, Anis Siti; Arbansyah, Arbansyah; Anitra, Vera; Rasit, Abdul; Mahmud, Hilal (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Straw, a byproduct of rice harvesting, is a waste material from farming activities that can be repurposed as animal feed and organic fertilizer. Rice straw, when supplemented with probiotics, can enhance feed nutrition, and its high potassium content contributes to the fertility of agricultural soil. The purpose of this community service activity was to increase the knowledge of the Sri Warga farmer group about the benefits of rice straw and the application of organic waste shredding machine technology. The physical shredding of rice straw improves its quality as animal feed and accelerates the composting process for organic fertilizer. The results of the community service activity demonstrated the farmer group members’ enthusiasm for adopting organic waste shredding machine technology and utilizing rice straw. There was a notable increase in their understanding of the dual benefits of rice straw—as a nutritious animal feed and as a resource for enhancing soil quality through organic fertilizers. This activity significantly improved the knowledge and awareness of Sri Warga farmer group members about the potential uses of rice straw. A post-activity questionnaire revealed that 95% of the farmer group members understood the benefits and nutritional content of rice straw for use as organic fertilizer or animal feed, compared to only 70% before the activity. This highlights the success of the community service initiative in empowering the Sri Warga farmer group wi